Magnetic resonance diffusion tractography of the preterm infant brain: a systematic review. (16th September 2013) - Pannek, Kerstin; Scheck, Simon M; Colditz, Paul B; Boyd, Roslyn N; Rose, Stephen E
<x xml:space="preserve">Abstract</x> Aim Preterm birth is associated with an increased risk of adverse neurodevelopmental outcomes. Diffusion magnetic resonance imaging (dMRI) combined with tractography can be used to assess non‐invasively white matter microstructure and brain development in preterm infants. Our aim was to conduct a systematic review of the current evidence obtained from tractography studies of preterm infants in whom MRI was performed up to term‐equivalent age. Method Databases were searched for dMRI tractography studies of preterm infants. Results Twenty‐two studies were assessed. The most frequently assessed tracts included the corticospinal tract, the corpus callosum, and the optic radiations. The superior longitudinal fasciculus, and the anterior and superior thalamic radiations were investigated less frequently. A clear relationship exists between diffusion metrics and postmenstrual age at the time of scanning, although the evidence of an effect of gestational age at birth and white matter injury is conflicting. Sex and laterality may play an important role in the relationship between diffusion metrics, early clinical assessment, and outcomes. Interpretation Studies involving infants of all gestational ages are required to elucidate the relationship between gestational age and diffusion metrics, and to establish the utility of tractography as a predictive tool. There is a need for more robust acquisition and analysis methods to improve the accuracy of assessing development of white matter pathways.